Hypothyroidism-associated testicular enlargement: is it a form of precocious puberty or not? A case report - Esen, İhsan; Demirel, Fatma (The Turkish Journal of Pediatrics, 2011)
In children with untreated hypothyroidism, the onset of puberty is usually delayed, but gonadotropin-independent precocious puberty may occur in children with severe hypothyroidism of long duration. The association of hypothyroidism, delayed bone age and gonadotropin-independent precocious puberty is defined as Van Wyk Grumbach syndrome (VWGS). VWGS has been described mostly in girls, and only seldom in boys. The manifestation of VWGS in boys is only testicular enlargement without substantial Leydig cell stimulation or testosterone secretion. We report a case of testicular enlargement due to obvious hypothyroidism secondary to autoimmune thyroiditis in a boy who presented with obesity. With this case report, we would like to emphasize that VWGS is not a real gonadotropin- independent precocious puberty in boys as it is in girls. Additionally, we would like to emphasize that delayed bone age is a special discriminating feature for differentiation of VWGS from the other causes of precocious puberty.